Application of Movement Method in Efforts to Improve Hadith Memorization at Tadika Al Fikh Orchard Port-Klang Selangor Malaysia - Munawir Pasaribu; Ade Gunawan (International Journal of Economic, Technology and Social Sciences (Injects), 2021)
This study aims to determine the application of the movement method in memorizing hadith for early childhood, the benefits of applying the movement method in memorizing hadith, the difficulties in applying the movement method to memorize hadith, and how to overcome difficulties in applying the movement method. This study uses a qualitative descriptive research method with data collection techniques using observation, interviews and documentation. Based on the findings and discussion in the research that has been done, it can be concluded that the application of the movement method in memorizing hadiths at Tadika Al Fikh Orchard Port-Klang Selangor Malaysia is an activity of teaching children short hadiths with hand movements so they can help interpret hadith readings. Namely hadiths about smiling, affection, don't be angry, cleanliness, and also hadiths about intentions. The steps in applying the movement method are: (1) preparation, namely making a daily learning activity plan (RPPH) preparing what hadiths will be taught (2) implementation, namely the teacher reading the hadiths along with their movements and the children follow them together (3) evaluation, which is carried out after the learning activities end. The benefits of memorizing using the movement method (1) Make it easy for children to memorize (2) Get used to children so that they always behave well and apply it in daily life (3) Balancing the child's left and right brain. (4) Develop children's physical motor. (5) Children are more enthusiastic in memorizing. Difficulties in applying the movement method in memorizing hadiths, namely: the teacher has difficulty in directing children to incorporate movement into hadiths. Ways to overcome difficulties in applying the movement method in memorizing hadiths (1) The teacher repeats memorization (2) The teacher directs children to incorporate movement into the hadith reading .